2021
DOI: 10.14245/ns.2142084.042
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neck Disability Severity Limits Extent of Postoperative Improvement Following Cervical Spine Procedures

Abstract: Objective: Our study aims to evaluate the impact of severity of preoperative Neck Disability Index (NDI) on postoperative patient-reported outcome measures (PROMs). Methods: A retrospective review of primary, elective, single or multilevel anterior cervical discectomy and fusion or cervical disc arthroplasty procedures between 2013 and 2019 was performed. Visual analogue scale (VAS) neck and arm, NDI, 12-item Short Form physical and mental composite score (SF-12 PCS and MCS), Patient-Reported Outcome Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…A prior study by Cha et al (2022) reported poor NDI to correlate with poor mental health both preoperatively and postoperatively in patients undergoing cervical spine surgery; however, this study did not assess the rate of improvement in mental health in patients with inferior disability scores. 22 Between groups, patients in the MD cohort reported significantly superior SF-12 MCS scores preoperatively and up to 6 months postoperatively, similar to the study performed by Cha et al (2021). The frequency of MCID achievement in SF-12 MCS was not significantly different between groups.…”
Section: Mental Functionsupporting
confidence: 67%
See 4 more Smart Citations
“…A prior study by Cha et al (2022) reported poor NDI to correlate with poor mental health both preoperatively and postoperatively in patients undergoing cervical spine surgery; however, this study did not assess the rate of improvement in mental health in patients with inferior disability scores. 22 Between groups, patients in the MD cohort reported significantly superior SF-12 MCS scores preoperatively and up to 6 months postoperatively, similar to the study performed by Cha et al (2021). The frequency of MCID achievement in SF-12 MCS was not significantly different between groups.…”
Section: Mental Functionsupporting
confidence: 67%
“…31 Similarly, a study, including patients who had undergone either ACDF or CDR, by Cha et al (2021) reported patients with greater preoperative NDI scores to experience significantly greater degrees of improvement in raw NDI score and greater rate of MCID achievement in NDI, VAS neck, and VAS arm when compared with patients with lower preoperative disability. 32 However, Cha et al (2021) noted that while a greater degree of improvement in NDI was observed, the severely disabled group continued to report inferior raw NDI scores along with inferior physical function, mental health, and pain scores at all postoperative periods compared with the less disabled cohorts. 32 With these prior findings in mind, we hypothesized that patients undergoing CDR with a greater preoperative disability may report inferior raw scores postoperatively when compared with less disabled patients, but may see a greater frequency of clinically meaningful improvement in disability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations